PENGAWETAN BATANG AREN DENGAN BAHAN PENGAWET TIPE CCA, CCB, DAN BFCA - Barly Barly (Jurnal Penelitian Hasil Hutan, 1989)
Aren timbers are suspectible to wood detercrating agents especially when used in contact with ground and/or exposed to the weather. Therefore, proper treatment is neccessary to protect them from insects and decaying organisms. The success of aren timber treatment depends on wood structure, treatment processes, and other factors.Treatment schedules of different processes were established through a series of experiment. For example, longer pressure period and higher preservative concentration are more suitable for products used in contact with ground than those used outdoor or without contact with the ground. In Anonymous (1987), the target CCA retention ranges from 3.3 to 10.6 kg/m3, and CCB from 6.4 to 11.4 kg/m3, and BFCA from 6.0 to 8.6 kg/m3, depend on preservatives and end products.The experimental results indicate that the retention of preservatives exceeds the minimum values of specification. Recomended treatment schedules for each process are presented.